(untitled) (Nigerian Journal of Technology, 2015)
The energy output of photovoltaic (PV) module at different tilt angles is presented in this paper. Enugu, the study area lies within Latitude 6o40’55.3”N & longitude 70 27’42.42’’E and is located in southern Nigeria. The paper analyses the solar radiation data estimated from sunshine hours and ambient temperature to predict the PV energy output at the site. The analysis showed that the best tilt angle for PV energy production is 60 if the module is fixed but if adjusted monthly, the best tilt angle for each month will be 300, 240, and 60 for (January to March),00for (April to September),180, 300 and 360for (October to December)respectively. It is found that adjusting the tilt angle of the module monthly to its optimum tilt will lead to an energy yield of 192.70 W/m2. This value represents about 3 % increase when compared to 186.86 W/m2obtained when the tilt angle was fixed. http://dx.doi.org/10.4314/njt.v34i4.24